Simplified model and analysis for the performance of Hofbauer–Vuilleumier heat pump. (July 2019) - Liao, Cheng; Jiang, Tao; Hofbauer, Peter; Ye, Wenlin; Liu, Jingping; Luo, Baojun; Huang, Yuexin
Abstract: Vuilleumier heat pumps can reduce the consumption of fossil combustion and thus have huge potential for applications in heating systems. However, it receives less attentions. In this paper, a Vuilleumier heat pumps with alternate move-and-stop motions (Hofbauer–Vuilleumier heat pump) was studied. A theoretical adiabatic model and a simple adiabatic model were derived. Both models were compared to the numerical adiabatic model and isothermal model. The results of theoretical adiabatic model agreed well with that of the numerical adiabatic model in terms of Q h, Q c, COP, pressure and temperature. The accuracy of the simple adiabatic model was relatively worse than the theoretical adiabatic model but much higher than the isothermal model. Furthermore, the effects of hot, warm and cold temperatures, initial pressure, dead volumes and various heat losses (regenerators' heat losses, displacers' shuttle losses, pumping losses and axial conduction losses) on the performance were investigated.